Revised checklist of the tiger moths of the Continental United States and Canada - Schmidt, B. Christian; Opler, Paul A. (Zootaxa, 2008)
The checklist of the Arctiinae (generally treated as the Arctiidae previously) of the continental United States and Canada is revised, incorporating a number of corrections and changes to publication dates and nomenclature as presented in the recent checklist of Ferguson and Opler (2006). Clemensia patella (Druce) is revised to synonomy under Clemensia albata Packard, Holoarctia sordida (McDunnough) is raised from synonomy under H. cervini (Fallou), and Arachnis apachea Clarke is transferred from synonomy under Arachnis verna Barnes & McDunnough to Arachnis citra Neumögen & Dyar. Palearctia Ferguson is synonomized under Holarctia M. E. Smith. The North American taxa previously treated as the tribe Arctiini are segregated into the subtribes Arctiina and Spilosomina. The genera Kodiosoma Stretch and Euerythra Harvey, previously treated as Arctiini, are transferred to the subtribe Phaegopterina.